2021
DOI: 10.1002/ejic.202001099
|View full text |Cite
|
Sign up to set email alerts
|

Variables of the Analytical Electrochemical Data Acquisition for Boron Subphthalocyanines

Abstract: The electrochemical behavior of boron subphthalocyanines (BsubPcs) has been investigated using cyclic voltammetry in the presence of various solvents, internal standards, supporting electrolytes, working electrodes, and sweep voltage scan rates. We have focused on halogenated BsubPcs (Cl−Cl6BsubPc, Cl−Cl12BsubPc, F−F6BsubPc, F−F12BsubPc) and a non‐halogenated baseline (Cl−BsubPc). Halogenated BsubPcs are of interest to the field due to their promising advances as organic electronic materials for applications b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The electrochemical properties of fully fluorinated F-F 12 BsubPc were used as a comparison point in analyzing the electrochemical properties of the peripherally fluorinated hybrids. For CV, we found that F-F 12 BsubPc had an irreversible oxidation potential at 1.536 V and two reversible reduction potentials at −0.460 V ( E 1/2,red 1 ) and −1.158 V ( E 1/2,red 2 ); these results are in excellent agreement with previously collected electrochemical data for F-F 12 BsubPc in similar CV conditions . Similar to F-F 12 BsubPc, both axially fluorinated hybrids, F-F 8 Bsub­(Pc 2 -Nc 1 ) and F-F 8 BsubPc, exhibit two reversible reduction potentials.…”
Section: Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The electrochemical properties of fully fluorinated F-F 12 BsubPc were used as a comparison point in analyzing the electrochemical properties of the peripherally fluorinated hybrids. For CV, we found that F-F 12 BsubPc had an irreversible oxidation potential at 1.536 V and two reversible reduction potentials at −0.460 V ( E 1/2,red 1 ) and −1.158 V ( E 1/2,red 2 ); these results are in excellent agreement with previously collected electrochemical data for F-F 12 BsubPc in similar CV conditions . Similar to F-F 12 BsubPc, both axially fluorinated hybrids, F-F 8 Bsub­(Pc 2 -Nc 1 ) and F-F 8 BsubPc, exhibit two reversible reduction potentials.…”
Section: Results and Discussionsupporting
confidence: 90%
“…The CV traces presented in this manuscript represent the trace of the third cycle. The resulting CV potentials were corrected to the half-wave oxidation potential of ferrocene/ferrocenium (Fc/Fc + ) ( E 1/2,ox = 0.547 V vs Ag/AgCl , ) that was used as an internal reference. For DPV, all potentials were corrected to the maximum potential of ferrocene, which was calculated to be 0.522 V vs Ag/AgCl using the following equation: E max = E 1 / 2 normalΔ E 2 , where E max is the maximum potential, E 1/2 is the known half-wave potential, and Δ E is the pulse amplitude .…”
Section: Methodsmentioning
confidence: 99%
“…The impact of different experimental variables such as the nature of solvents, internal standards and electrolytes, the type of working electrodes and the scan rate on the electrochemical behavior of various SubPc derivatives was systematically investigated by Bender and co-workers, who established a standard operating procedure for data acquisition. 208…”
Section: Subphthalocyaninesmentioning
confidence: 99%
“…80,83,206,207 The impact of different experimental variables such as the nature of solvents, internal standards and electrolytes, the type of working electrodes and the scan rate on the electrochemical behavior of various SubPc derivatives was systematically investigated by Bender and co-workers, who established a standard operating procedure for data acquisition. 208 The redox gap of SubPc is larger than that of Pcs, being the former of about 2.1 eV and the latter of approximately 1.7 eV. 1 Several techniques have been employed for the estimation of the absolute HOMO and LUMO energy levels of SubPcs, such as cyclic voltammetry in solution or photoelectron spectroscopy onto highly ordered pyrolytic graphite (HOPG) substrates.…”
Section: Excited Statesmentioning
confidence: 99%
“…For this purpose, we prepared and evaluated three different SubPcs ( Figure 1 ) with varying electronic and supramolecular properties. In particular, we synthetize SubPcs functionalized with either six or twelve peripheral fluorine or chlorine atoms ( Cl-SubPcF 6 , Cl-SubPcF 12, and Cl-SubPcCl 12 ), since it has been previously demonstrated that they present good supramolecular organization and low-lying LUMO levels ( Bukuroshi et al, 2021 ). In combination with C 60 , these SubPc materials are then implemented as ETM in PSC devices based on a solution processed PVK (CsFAMAPbIBr) active layer.…”
Section: Introductionmentioning
confidence: 99%